2002
DOI: 10.1074/jbc.m205394200
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of HIV-1 Receptor Function through Cooperation between Different Forms of the CCR5 Chemokine Receptor

Abstract: Interaction of the human immunodeficiency virus (HIV-1) envelope glycoproteins with the CCR5 chemokine receptor, a G-protein-coupled receptor, triggers a membrane fusion process and virus entry. Cooperation for HIV-1 receptor activity was observed when two forms of CCR5 were coexpressed, either the wild-type (WT) receptor and a defective mutant with deletion of the amino-terminal (NT) extracellular domain or the latter ⌬NT mutant and a human-mouse CCR5 chimera bearing the NT domain from human CCR5. Cooperation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 64 publications
0
9
0
1
Order By: Relevance
“…The latter are CCR5 transfectants of a murine pre-B-cell lymphoma line (116), so that post-translational modifications of CCR5 may be subtly different from what happens in primary human cells. Again, there is precedent for chemokine receptors, including CCR5, existing in multiple isoforms and conformations (6,10,11,18,36,63,64,67,70). If this is the explanation, then full AD101 resistance involves HIV-1 acquiring the ability to use a distinctive configuration of CCR5 that, somehow, is not affected by AD101 and other small-molecule inhibitors while still being vulnerable to CCR5-specific MAbs and RANTES.…”
Section: Discussionmentioning
confidence: 99%
“…The latter are CCR5 transfectants of a murine pre-B-cell lymphoma line (116), so that post-translational modifications of CCR5 may be subtly different from what happens in primary human cells. Again, there is precedent for chemokine receptors, including CCR5, existing in multiple isoforms and conformations (6,10,11,18,36,63,64,67,70). If this is the explanation, then full AD101 resistance involves HIV-1 acquiring the ability to use a distinctive configuration of CCR5 that, somehow, is not affected by AD101 and other small-molecule inhibitors while still being vulnerable to CCR5-specific MAbs and RANTES.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, receptor oligomerization is constitutive, i.e. independent of receptor activation, and does not require the N-terminal extracellular domain (36). By using a functional complementation approach we demonstrate that a CCR5-⌬NT mutant deficient in ligand binding undergoes GRK-mediated phosphorylation if this receptor is co-expressed together with a different receptor mutant that recruits receptor kinases to the CCR5 homooligomer at the plasma membrane (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have suggested that many GPCRs form homo-and heterodimers and that the dimerization contributes to modulation of receptor function (10). Dimer-forming receptors include (but are not limited to) ␤ 2 -adrenergic receptor (11), the ␦ opioid receptor (12), somatostatin receptors (13), CXCR4 (14), CCR2 (15), and CCR5 (16,17). The last three of these are chemokine receptors that mediate chemotaxis toward their ligands in a manner similar to FPR.…”
mentioning
confidence: 99%